Impact of adenotonsillectomy on nocturnal enuresis in children with sleep‐disordered breathing: A prospective study. (1st March 2016) - Park, Sungchan; Lee, Jung Min; Sim, Chang Sun; Kim, Jae Gi; Nam, Jung Gwon; Lee, Tae‐Hoon; Han, Myung Woul; Kwon, Joong Keun; Lee, Jong Cheol
Abstract : Objectives/Hypothesis: To investigate the relationship between sleep‐disordered breathing (SDB) and nocturnal enuresis (NE) in children and to prospectively evaluate the effectiveness of adenotonsillectomy on resolving enuresis in indicated SDB patients with NE. Methods: We prospectively collected data from 183 children (121 males, mean age 8.17 ± 2.84 years) who underwent adenotonsillectomy to treat SDB between July 2011 and July 2013, and analyzed the prevalence of NE. Before and 3 months after surgery, all parents were requested to answer a self‐reported SDB scale questionnaire (22 questions, 0–22 points) and a NE questionnaire (episodes of enuresis per month). Paired t test, Student t test, and Chi‐square test were used to analyze the data. Results: Overall prevalence of NE was 9.3% (17 patients) preoperatively and 1.5% postoperatively (four patients). After adenotonsillectomy, prevalence of NE and the mean SDB scale were significantly decreased (both P values < 0.001). After adenotonsillectomy, 13 of the 17 NE patients (76.5%) showed complete resolution. There was significantly higher prevalence of NE in patients with obstructive sleep apnea (OSA) than those without OSA (13.1%, 14 of 107 vs. 3.9%, 3 of 76; P = 0.036). Conclusion: There is strong association between NE and SDB, and adenotonsillectomy can markedly improve enuresis in the majority of children with NE and SDB. Levels of Evidence: 4. Laryngoscope, 126:1241–1245, 2016